2018
DOI: 10.1016/j.abrep.2018.06.004
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric assessment of the Internet Gaming Disorder diagnostic criteria: An Item Response Theory study

Abstract: Internet Gaming Disorder (IGD) has been recognized by the American Psychiatric Association (APA) as a tentative disorder in the latest fifth revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). In order to advance research on IGD, the APA has suggested that further research on the nine IGD criteria to investigate its clinical and empirical feasibility is necessary. The aim of the present study was to develop the Polish the Internet Gaming Disorder Scale–Short-Form (IGDS9-SF) and scrut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 67 publications
7
84
1
3
Order By: Relevance
“…Results of the present study are in line with the previous studies, which also showed that the IGDS-SF9 [13], BSMAS [23], and SABAS [28] are psychometrically robust. More specifically, all the previous findings [15][16][17][18]21] and the findings in the present study demonstrated that all the three instruments had a unidimensional structure.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Results of the present study are in line with the previous studies, which also showed that the IGDS-SF9 [13], BSMAS [23], and SABAS [28] are psychometrically robust. More specifically, all the previous findings [15][16][17][18]21] and the findings in the present study demonstrated that all the three instruments had a unidimensional structure.…”
Section: Discussionsupporting
confidence: 84%
“…Although the internal consistency between findings in the present study and others are comparable [15][16][17][18], the present study revealed relatively high floor effects (21%) as compared with previous studies [11,17]. More specifically, another study using a Hong Kong population using C-IGDS showed the floor effect at 0.8%; one study on Iranian population using IGDS-SF9 also showed the floor effect at 0.8% [17].…”
Section: Igds-sf9supporting
confidence: 51%
See 1 more Smart Citation
“…Due to the Likert-type scale used in MisoQuest, we used the Graded Response Model (GRM) for polytomous data [28]. In this model, difficulty parameters indicate the threshold of a latent trait between answer choices and the discrimination parameter reflects the degree to which an item discriminates individuals across the latent trait range [29]. To compare the fit of the two models (constrained and unconstrained), the Akaike's Information Criterion (AIC) [30] and Bayesian Information Criterion (BIC) [31] were calculated.…”
Section: Data Management and Analytic Strategymentioning
confidence: 99%
“…Так, наприклад, для визначення онлайн-та офлайн-ігрової залежності досить поширеними є наступні клінічні симптоми: надмірна зайнятість відеоіграми; відчуття неприємних емоцій під час відсутності відеозв'язку або формування синдрому відміни; необхідність витрачати все більше часу на відеоігри або розвиток толерантності; наявність невдалих спроб самоконтролю; втрата зацікавленості попередніми хобі та захопленнями, що може супроводжуватися відмовою займатися іншими розважальними видами діяльності; продовження надмірного використання відеоігор, незважаючи на появу побутових проблем; обман близьких, терапевтів чи інших осіб щодо кількості проведеного часу в віртуальному просторі; використання відеоігор для втечі та усунення негативного настрою або поява явища ескейпінгу; формування загрози щодо особистих стосунків, втрати роботи чи ускладнення здобуття освіти внаслідок діяльності в відеоіграх. Встановлено, що серед осіб з віртуальною залежністю спостерігаються нижча соціальна підтримка та якість життя, що пов'язані з розладами здоров'я, антисоціальною поведінкою, психоемоційними розладами, соціальною фобією (наприклад, особи з синдромом Хікікоморі), зниження загального рівня задоволеності життям та низькою самоефективністю, наявні супутні розлади щодо вживання хімічних речовин тощо [20].…”
Section: симптоми віртуальної залежностіunclassified